The Effect of the Inside Outside Circle (Io) Model Assisted by Short Video Microlearning on the Motivation of Indonesian Language Learning of Grade IV Students at SDN 1 Sri Kencono Central Lampung - Rosita; Nurul Hidayah; Yudesta Erfayliana (Journal of Education and Teaching Learning, 2026)
This research is motivated by the low motivation to learn Indonesian language of fourth grade students at SDN 1 Sri Kencono, Central Lampung, which is shown through the lack of enthusiasm, activeness, and courage to ask questions during the lesson. The formulation of the problem in this study is whether there is an influence of the Inside Outside Circle (IOC) learning model assisted by short video Microlearning on the motivation to learn Indonesian language of fourth grade students. The aim of the research is to determine the influence of the Inside Outside Circle (IOC) learning model assisted by short video Microlearning on the motivation to learn Indonesian language of fourth grade students at SDN 1 Sri Kencono, Central Lampung. This research uses a quantitative approach with a Quasi Experiment type and a pretest-posttest control group design. Data were collected through a learning motivation questionnaire, then analyzed using validity tests, reliability tests, normality tests, homogeneity tests, and hypothesis tests with paired t-tests. The results of the study indicate that the implementation of the Inside Outside Circle (IOC) model assisted by short video microlearning has a positive influence on students' learning motivation, marked by increased activity, attention, and learning participation during learning. Thus, it can be concluded that the Inside Outside Circle (IOC) model assisted by short video microlearning is effective in increasing the motivation to learn Indonesian in fourth grade students.